The impact of monetary policy stance, financial conditions, and the GFC on investment-cash flow sensitivity* - Gul, Selcuk; Tastan, Huseyin (ELSEVIER, 2020)
This paper investigates the role of internal finance in determining firms' fixed capital investments in an emerging economy. Using a comprehensive panel data set from Turkish unlisted small and medium-sized enterprises (SMEs) in the manufacturing sector, we estimate a set of dynamic firm investment models in which the marginal impact of cash flow on investment is allowed to vary with the central bank's monetary policy stance, financial conditions at the macro level and the Global Financial Crisis (GFC). According to the system-GMM estimation results, the sensitivity of investment to cash flow is positive and statistically significant, implying that firms are constrained by internal finance. Empirical results suggest that the degree of investment-cash flow sensitivity significantly varies with the monetary policy stance. While the investment-cash flow sensitivity declines during periods of expansionary monetary policy for financially constrained firms, the evidence is not conclusive for less-constrained firms that can access external finance relatively easily. We also find that investment-cash flow sensitivity declines when broader macro-financial conditions are relatively supportive. Furthermore, firms' cash flow needs grow considerably during recessionary periods (e.g., the GFC) compared to expansionary periods due to less availability of external funds.
Keywords: Investment-cash flow sensitivity; Financing constraints; Monetary policy stance; Financial conditions index; TRADE CREDIT CHANNEL; FIRM INVESTMENT; TRANSMISSION EVIDENCE; INVENTORY INVESTMENT; CONSTRAINTS EVIDENCE; GLOBAL ENGAGEMENT; PANEL-DATA; LEVERAGE; DEBT; DECISIONS; Business & Economics